Rindi - Forth, G.L (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1981)
The author describes Rindi culture within an analytic framework that illustrates connexions between, and common principles among, often apparently disparate realms of thought and action.